1899 Annotated Statutes of the Indian Territory, at 241, ch. 19, pt. 49, § 1234 - (:unkn) unknown (My University, 1899)
If any person shall be found hunting with a gun, with intent to kill game, or shooting for amusement on the Sabbath day, on conviction thereof, he shall be fined in any sum not less than five nor more than twenty-five dollars for each separate offense.
Keywords: HUNTING REGULATION